2007
DOI: 10.4314/nifoj.v25i1.33655
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical profile of some green leafy vegetables in South East, Nigeria

Abstract: The potential of eight common green leafy vegetables (GLV) in the raw and cooked forms as natural source of phytochemicals was assessed. The vegetables studied were the common ones found in southeast Nigeria and they included Ugu, Nchanwu, Okazi, Utazi, Oha, Nturukpa, Ahihara, and Onugbo. The vegetables were assessed for the following phytochemicals: alkaloid, steroid, tannin, anthocyanin, carotenoids and flavonoid. The phytochemical content of the vegetables varied significantly (p=0.05) among the GLV. Onugbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 12 publications
1
35
3
Order By: Relevance
“…They have the ability to scavenge hydroxyl radicals, super oxide anions and lipid peroxy radicals (Okwu, 2004;Okwu and Josiah, 2006), therefore supports its antioxidant activity. The flavonoid content of the leaves of Ficus capensis therefore supports its use for protection against diseases such as cancer, inflammation and atherosclerosis (Onyeka and Nwambekwe, 2007). The presence of alkaloids (422.12mg/100g) in the leaves of Ficus capensis supports the findings by Oyeleke et al, (2008), that the antibacterial activity of this plant may be attributed to the presence of alkaloids.…”
Section: Discussionsupporting
confidence: 76%
“…They have the ability to scavenge hydroxyl radicals, super oxide anions and lipid peroxy radicals (Okwu, 2004;Okwu and Josiah, 2006), therefore supports its antioxidant activity. The flavonoid content of the leaves of Ficus capensis therefore supports its use for protection against diseases such as cancer, inflammation and atherosclerosis (Onyeka and Nwambekwe, 2007). The presence of alkaloids (422.12mg/100g) in the leaves of Ficus capensis supports the findings by Oyeleke et al, (2008), that the antibacterial activity of this plant may be attributed to the presence of alkaloids.…”
Section: Discussionsupporting
confidence: 76%
“…However, red cabbage contains high amount of phytic acid (30.36 ± 0.90) than Green and Chinese varieties. Table 3 shows that rats fed with Chinese, green and red cabbage extracts (Groups A,B, and C) have reduced PCV and haemoglobin levels at the end of the 14days of experimental period compared to the normal/control group D, results from the table 4 showed that there were significant increase in the serum levels of the plasma enzymes activities and other biochemical indices for the case samples when compared to the control group, revealing health problems of various degree which may be occasioned by liver and pancreatic damage [8]. The disease conditions associated with the elevated determined biochemical parameters are as follows; increased levels of alkaline phosphatase may indicate cholestasis, liver tumors and obstructive biliary disease.…”
Section: Discussionmentioning
confidence: 94%
“…All the alkaloids in T. occidentalis varied in the different growth medium. The total alkaloids (11.614 g/100g NM, 9.082 g/100g HS) obtained in T. occidentalis using HPLC was higher compared to other works (Onyeka and Nwambekwe, 2007;Otitoju et al, 2014;Odufuwa et al, 2013), which reported 0.81 g/100g, 0.04 g/100g and 0.039 g/100g, respectively for total alkaloids in T. occidentalis. Also, Oduse et al (2012) reported 13.83 mg/kg for Cnidoscolus aconitifloina and 10.13 mg/kg for Vernonia amygdalina.…”
Section: Resultsmentioning
confidence: 38%